PERILAKU PETANI PADI ORGANIK TERHADAP RISIKO DI KECAMATAN SUSUKAN KABUPATEN SEMARANG - Ermelinda Bola; Tinjung Mary Prihtanti (SOCA: Jurnal Sosial Ekonomi Pertanian, 2019)
The study aims to analyze the behavior of farmers toward the risk of organic rice farming and to investigate and its determinant factors the behavior of farmers toward the risk of organic rice farming in Susukan District, Semarang Regency. In this study, the respondents used were 76 organic rice farmers in Susukan District. The research method used is a survey. The research location was chosen by purposive sampling. Sampling is done through simple random sampling. The risk behavior analysis method uses the Cobb Douglas production function approach then analyzed by multiple linear regression and to measure farmers' behavior towards risk using the Moscardi and de Janvry methods. To find out the factors that influence farmers' behavior towards risk using multiple linear regression analysis. The results showed that organic rice farmers in Susukan Major District avoided risk or refused risk (risk averter), which was 76 farmers (100%) even though organic rice farming was at risk. Land area and farmer's income are significant and influence farmers' behavior towards risk.